Syphilis on the big screen: an audiovisual representation of the health-disease process - Braz, Laísi Catharina da Silva Barbalho (2021)
Introduction: In addition to its entertainment role, cinema has a strong relationship with history and a significant social appeal, as it provides the possibility of discussing the matters of society in a dynamic way. Important historical facts such as wars, technological development and pandemics have become recurrent themes on the screens, since they impact various social groups. By the same token, the theme of sexually transmitted infections has been extensively explored in motion pictures, portraying the origins of diseases, their impact on the social environment, and how the health-disease process unfolds. Objective: This study aimed to perform a critical analysis of audiovisual works that bring syphilis in its plot, in order to identify and discuss the evolution of the health-disease process throughout history, as well as its representation in the cinematic perspective. Methods: A descriptive analysis of audiovisual works was carried out along with a bibliographic search. Results: The corpus of the study consisted of four films, the feature films: "La Pelle", by Liliana Cavani; "Miss Evers' Boys", by Joseph Sargent; "Heleno: O Príncipe Maldito", by José Henrique Fonseca; and "Dr. Ehrlich's Magic Bullet", by William Dieterle. In all four works, we have different perspectives of the same health problem, but in different scenarios. Conclusion: Reflecting about these scenarios, as well as the real world, helps us to understand and search for what each of the represented groups' needs in order to face the disease more objectively and effectively. Keywords: syphilis; motion pictures; health-disease process; sexually transmitted infections.